2016
DOI: 10.1016/j.bbamem.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation of nonfacilitated membrane permeation

Abstract: This is a review. Non-electrolytic compounds typically cross cell membranes by passive diffusion. The rate of permeation is dependent on the chemical properties of the solute and the composition of the lipid bilayer membrane. Predicting the permeability coefficient of a solute is important in pharmaceutical chemistry and toxicology. Molecular simulation has proven to be a valuable tool for modeling permeation of solutes through a lipid bilayer. In particular, the solubility-diffusion model has allowed for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(154 citation statements)
references
References 188 publications
5
146
0
Order By: Relevance
“…These results are in line with previous simulations. 46,47 The TIP3P-FB and TIP4P-FB water models have viscosity/self-diffusion coefficients that are much closer to the experimental values and the diffusivity of the permeating water molecule is lower accordingly. Using these more realistic water models, the water solute diffuses at a faster rate at the center of the bilayer than in solution, opposite to the trend predicted using the TIP3P model.…”
Section: Water Permeabilitysupporting
confidence: 55%
See 1 more Smart Citation
“…These results are in line with previous simulations. 46,47 The TIP3P-FB and TIP4P-FB water models have viscosity/self-diffusion coefficients that are much closer to the experimental values and the diffusivity of the permeating water molecule is lower accordingly. Using these more realistic water models, the water solute diffuses at a faster rate at the center of the bilayer than in solution, opposite to the trend predicted using the TIP3P model.…”
Section: Water Permeabilitysupporting
confidence: 55%
“…42 Several theoretical models have been developed to predict the rates of permeation from molecular simulations, although the solubility-diffusion model has been particularly popular. 7,[43][44][45][46] This model predicts the rate of permeation from the potential of mean force and the diffusivity of the permeating solute as a function of its position, z, along the transmembrane axis. The effect of the water model on the diffusivity is apparent in transmembrane diffusivity profile (|z| > 20Å) The TIP3P water model has a viscosity coefficient that is much lower than the experimental value (η T IP 3P = 0.321 mPa·s vs η exptl = 0.896 mPa·s ), so its rate of diffusion in the solution and at the lipid-water interface is unrealistically fast (D H 2 O = 6.05 cm 2 /s).…”
Section: Water Permeabilitymentioning
confidence: 99%
“…In spite of all these difficulties, MD simulations have been used to calculate permeability coefficients [48]. A good summary of the prediction of the non-facilitated membrane permeation of several solutes is provided elsewhere [228]. The agreement with experimental methods was qualitatively good, but quantitative agreement can be poor, as deviations by an order of magnitude [48], or even larger [229], were observed.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Estimates of W ( z ) and D ( z ) can be predicted using molecular dynamics (MD) simulations. 2,6,7 While the ISD has been applied successfully in many studies, 2,5,822 recent work by various groups has suggested that the dynamics of crowded environments, such as inside the bilayer, may exhibit more complicated behaviors. 2,23 The dynamics inside of the bilayer has not, to the best of our knowledge, been probed in detail.…”
Section: Introductionmentioning
confidence: 99%